2015
DOI: 10.4049/jimmunol.1500365
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Binding Protein Secreted by Breast Cancer Cells Inhibits Monocyte-Derived Fibrocyte Differentiation

Abstract: To metastasize, tumor cells often need to migrate through a layer of collagen-containing scar tissue which encapsulates the tumor. A key component of scar tissue and fibrosing diseases is the monocyte-derived fibrocyte, a collagen-secreting pro-fibrotic cell. To test the hypothesis that invasive tumor cells may block the formation of the fibrous sheath, we determined if tumor cells secrete factors that inhibit monocyte-derived fibrocyte differentiation. We found that the human metastatic breast cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 113 publications
(137 reference statements)
1
43
0
Order By: Relevance
“…Early Northern blot studies showed abundant LGALS3BP mRNA signal in many normal human tissues, and especially prominent expression was seen in lung and gastrointestinal tissues. 13 This is in accordance Collagen-IV, -V, -VI Influences cell-cell or cell-matrix interaction 20 Cyclophilin C a Regulates cyclophilin C functions 16,94 DC-SIGN b,c Inhibits maturation of dendritic cells, inhibits differentiation of monocyte-derived fibrocytes, 34,60 E-cadherin-p120catenin…”
Section: Expression Pattern Of Gal-3bpmentioning
confidence: 84%
See 1 more Smart Citation
“…Early Northern blot studies showed abundant LGALS3BP mRNA signal in many normal human tissues, and especially prominent expression was seen in lung and gastrointestinal tissues. 13 This is in accordance Collagen-IV, -V, -VI Influences cell-cell or cell-matrix interaction 20 Cyclophilin C a Regulates cyclophilin C functions 16,94 DC-SIGN b,c Inhibits maturation of dendritic cells, inhibits differentiation of monocyte-derived fibrocytes, 34,60 E-cadherin-p120catenin…”
Section: Expression Pattern Of Gal-3bpmentioning
confidence: 84%
“…The study was conducted in a cancer context, and the authors proposed that the Gal‐3BP–DC‐SIGN interaction contributes to the development of tolerogenic microenvironment for Gal‐3BP‐overexpressing colorectal cancer cells . Binding of Gal‐3BP to DC‐SIGN has also been reported to suppress the differentiation of monocyte‐derived fibrocytes, further indicating that Gal‐3BP may have immunosuppressive functions.…”
Section: Gal‐3bp and Innate Immunitymentioning
confidence: 99%
“…Similar to the expression in metastatic tumor cells, exosome subsets were enriched with sialylated glycoproteins, supporting the role of these structures in exosome-mediated cellular recognition. One predominant sialoglycoprotein previously identified in exosomes 25, 35 , the galectin-3-binding protein (LGALS3BP), a modulator of cell communication and immune responses 36, 37 , was highly enriched in exomeres. This ligand could mediate the specific interaction of exomeres with target cells through proteins, such as collagens, fibronectin, nidogen, galectin-3 and integrin beta-1 38,39 .…”
Section: Discussionmentioning
confidence: 98%
“…Gal-3 has been considered a tumor-associated antigen of malignancy level in breast cancer, and is implicated in aspects, such as angiogenesis [219], adhesion [220], invasion [221], apoptosis inhibition [222], migration [223], and therapeutic resistance [224]. Chen et al, through hydrazide-based chemistry method combined with liquid chromatography tandem-mass spectrometry (LC-MS/MS), identified 72 unique N-linked glycoproteins that were significantly regulated in triple negative breast cancers, among which is LGALS3BP.…”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 99%